Estresse e satisfação no trabalho de profissionais que exercem a função de gestores na área comercial - Lelis, José Wilson Franca (2013)
The professional management level is inserted into a corporate culture in which, in general, people work longer hours and harder. The need to adapt to this frantic pace, coupled with the challenge of the need for survival of the individual and the organization, highlight two aspects that are present in the working relationship, particularly in the performance of the commercial manager: stress and job satisfaction. The objectives of this study, of descriptive nature and quantitative approach, were: to study the stress level and the level of satisfaction related to work and to check if there is a relationship between occupational stress and job satisfaction of managers. The sample population of the study was made up of commercial managers that, after contacted by e-mail, electronic questionnaire sent, inserted into the Google Form tool. The answered to the questionnaire was made up of three parts: profile of respondents, Work Stress Scale and Job Satisfaction Scale. Among the 114 participants of the study, the average age was 42.7 ± 8.8 years. Most of the participants were male (69.3%). They attended graduate studies (74.6%) and work in private (93.8%), or large or medium size (87.7%). The average stress score was of 2.24 ± 0.61, ranging from 1.04 to 3.83, regarded as an average level of stress. Considering the five dimensions of job satisfaction the average scores of the following dimensions were classified as state of indifference, there is, neither satisfied nor dissatisfied: satisfaction with colleagues (4.70), with the heads (4.69), with the nature of the work (4.67) and with the promotions (4.12). The satisfaction with salary dimension with lowest average score (3.83) tends to signal dissatisfaction in the studied group. The Spearman correlation test demonstrated that stress presents a negative and statistically significant correlation with the five dimensions of satisfaction at work. The correlaction is inverse, that is, the smaller the job satisfaction, the greater stress, confirming the hypothesis of the study. The study results indicate the importance of the organization and of the people involved in the process in dealing with the issue of stress and satisfaction in order to achieve a level of excellence in the results of the organization function